Entering First-in-Human Clinical Study With a Single-Strain Live Biotherapeutic Product: Input and Feedback Gained From the EMA and the FDA - Paquet, Jeanne-Céleste; Claus, Sandrine P.; Cordaillat-Simmons, Magali; Mazier, Wilfrid; Rawadi, Georges; Rinaldi, Laure; Elustondo, Frédéric; Rouanet, Alice (Frontiers in Medicine, 2021)
During the last decade, a plethora of novel therapies containing live microorganisms as active substance(s) has emerged with the aim to treat, prevent, or cure diseases in human beings. Both the Food and Drug Administration (FDA) and the European Directorate for the Quality of Medicines and Health Care (EDQM) codified these biotherapies as Live Biotherapeutic Products (LBPs). While these innovative products offer healthcare opportunities, they also represent a challenge for developers who need to set the most suitable designs for non-clinical and clinical studies in order to demonstrate a positive benefit/risk ratio through relevant quality, safety, and efficacy data that are expected by the drug competent authorities. This article describes how YSOPIA Bioscience, supported by the Pharmabiotic Research Institute (PRI), addressed the regulatory challenges during the early development phase of their single-strain LBP, Xla1, in order to obtain the necessary authorizations to bring this drug to the clinical stage.